Exercise-induced syncope: Case report (2011)
Exercise-induced syncope is a condition that should alert the treating physician; structural cardiac abnormalities that predispose to sudden death should be discarded, and the presence of arrhythmias that may potentially cause this condition are evaluated. In patients over 35 years, coronary and valvular disease are ruled-out as a possible cause of syncope associated with exercise. In subjects who train frequently, increased vagal tone is a common adaptive condition that may sometimes cause cardio-inhibitory syncope associated with exercise, whose presentation may vary from bradyarrhythmia to asystolia, thereby providing a diagnostic challenge.